Upaya Penanganan Pola Nafas Tidak Efektif Pada Sirosis Hepatitis Di Rsud Dr. Soehadi Prijonegoro Sragen - Pradna, Ambar Novita Putri; , Arief Wahyudi Jadmiko, S. Kep., Ns., M. Kep (2016)
Background: According to the WHO in 2008, couse of the death in the world, one of them is cirrhosis hepatis diseases. The diaseases ranks 18th in the world. Cirrhosis hepatis coused by hepatitis virus. The complication that can couse hematemesis and melena, besides that also can couse of increasing pressure of part and from bleeding can reduce the level of hemoglobin in the blood, so that the ogxygen supply to the brain is inadequate, that can couse breating ineffective. Objective: Providing nursing care in patients with a diagnosis of cirrhosis hepatis in space Melati VI B Prijonegoro Soehadi hospital located in Sragen District. Methods: Using data collection methods attractions in Soehadi Prijonegoro hospitals starting from 28 March 2016 until 31 March 2016 in Jasmine Room VI B, purpose so that data can be collected well and directed, should be done categorization or classification of data based on the identity of the client, a major complaint, medical history, physical, psychological, social, spiritual, intelligence, results of check up, and other special condition, assessment methods using either diagnose allo and auto anamnesis. Results: After nursing actions during 3x24 hours to patients with liver cirrhosis pattern Ineffective breathing connected with hyperventilation problems. Management that made to over come ineffective breathing is by the way of teaching a deep breath and focus on semi fowler, beside that can over come by preventing bleeding that repeatedly to the patient with cirrhosis hepatis. Conclusion: Problem of nursing breathing innefective connected with hyperventilation is not resolved families still need to exercise care in the home to prevent bleeding was repeated and in order to increase hemoglobin (Hb) by providing foods that contain iron such as green leafy vegetables, liver, egg yolk. The cooperation between the family and the medical team is able to prevent or reduce the risk of recurrent bleeding.